The most excellent and lamentable tragedy of Romeo & Juliet : a play by William Shakespeare - Hinds, Gareth, 1971- (Candlewick Press, 2013)
"She's a Capulet. He's a Montague. But when Romeo and Juliet first meet, they don't know they're from rival families-- and when they find out, they don't care. Their love is honest and raw and all-consuming. But it's also dangerous. How much will they have to sacrifice before they can be together? In a masterful adaptation faithful to Shakespeare's original text, Gareth Hinds transports readers to the sun-washed streets and market squares of Shakespeare's Verona, vividly bringing the classic play to life on the printed page."--